Effect of cryogenic treatment of tungsten carbide tools on cutting force and power consumption in CNC milling process. Issue 1 (1st January 2018) - Mukkoti, Vishnu Vardhan; Sankaraiah, G.; Yohan, M.
Abstract: In this paper, the effect of Deep Cryogenic Treatment (DCT) soaking duration on tungsten carbide end mill cutters on cutting forces and power consumption during machining P20 mold steel in CNC milling machine is investigated and optimized the process parameters. The data collected for the study are based on Box–Behnken design of response surface methodology. Cutting forces and power consumption are considered as important performance measures which are functions of decision variables viz. cutting speed, feed, depth of cut, and end milling cutting tools subjected to different soaking duration. The percentage contribution is calculated based on ANOVA to identify most influencing parameter on cutting forces and power consumption. The study revealed that cryogenic soaking duration exhibits most significant effect on cutting forces and power consumption followed by cutting speed, feed, and depth of cut. Regression analysis is carried out to relate the process variables and performance measures. Finally, a non-dominated sorting Algorithm (NSGA-II) is proposed to optimize the process variable to obtain the desired optimal solutions. The results indicate DCT tool soaked for longer duration is minimizing the cutting forces and power consumption when compared to untreated tool.